Pengungkapan Sustainability Report Berdasarkan GRI Standards 300 Pada PT.Bank Rakyat Indonesia dan PT. Bank Tabungan Negara - Rizka Aulia; Sangra Puttidia Daulay (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study examines sustainability report disclosures based on GRI Standards 300 (Environmental Topics) in PT Bank Rakyat Indonesia (Persero) Tbk and PT Bank Negara Indonesia (Persero) Tbk for 2024. Using content analysis, the reports were assessed against 31 GRI 300 indicators. The findings show that BBRI disclosed all indicators (100%), while BBNI disclosed 27 indicators (87%), with limited disclosure in material and energy aspects. These results indicate variations in environmental reporting compliance and highlight the need for improved consistency and completeness to enhance corporate transparency and accountability.